A study on the convective structure of the atmosphere over the West Coast of India during ARMEX-I - MOHANTY, U. C.; SAM, N. V.; DAS, S.; BASU, S. (MAUSAM, 2005)
Onset of south west monsoon (SWM) over Kerala is associated with intense convection followed by heavy rainfall over the west-coast of India. The intense rainfall events are usually associated with meso-scale convective systems embedded in large scale synoptic system over the Arabian Sea. Such deep and intense cumulus convection can have an important effect on the dynamics and energetics of large-scale atmospheric systems, because of the large magnitudes of the energy transformations associated with changes of phase of water in precipitating cumulus clouds as well as the strong updrafts and downdrafts in the troposphere. The prime objective of this study is to understand the convective structure (active/suppressed) of the atmosphere over the west-coast of India during ARMEX-I (Arabian Sea Monsoon Experiment). This study uses an approach to obtain the average structure of a cloud cluster and its interaction with the environment that enables in distinguishing the variation of kinematic and convective parameters from suppressed to convectively active process. Upper air observations obtained from four coastal land stations viz., Bombay, Goa, Mangalore and Trivandrum, alongwith that obtained over ORV Sagar Kanya are used to calculate both the convective and the kinematic parameters at the centre of the polygon formed by these observation locations. Time averaged circulation kinematic parameters and vertical velocity during active and suppressed convective phases off the west coast of India were discussed. The apparent heating and the apparent moisture sink are also estimated through residuals of the thermodynamic equations during intense and weak phases of SWM.